Students’ Speaking Skills through Communicative Language Teaching - Basir, Achmad (Celebes Scholar pg, 2024)
This study was designed to increase the English speaking of students by implementing Communicative Language Teaching (CLT) approach in the second grade of Department of Dental Nurse Politeknik Kementerian Kesehatan Makassar. The subject taught was the English for Dental Nurse and the sample used in this study was class A as a control group and class B as an experimental group. This study implemented quasi experimental design with nonequivalent control group design. The result of this study showed significant greater improvement in students’ English speaking by implementing Communicative Language Teaching approach for experimental class than implementing Grammar Translation Method for control group. The study’s findings demonstrated that Grammar Translation Method was not as successful at increasing students’ speaking as Communicative Language Teaching (CLT).